1996
DOI: 10.1093/oxfordjournals.humrep.a019515
|View full text |Cite
|
Sign up to set email alerts
|

Andrology: Pituitary-testicular axis in men with  -thalassaemia major

Abstract: Delayed puberty and hypogonadism are frequently observed in patients with homozygous beta-thalassaemia. We evaluated the pituitary-testicular axis in 30 thalassaemic men, aged from 17 to 35 years who were regularly transfused and underwent chelation therapy, while emphasis was given to pituitary reserves of gonadotrophins and the correlation of hormones with serum ferritin (SF). The investigation included endocrinological examination, evaluation of serum basal levels of follicle stimulating hormone (FSH), lute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…However, only 74% of patients developed primary or secondary amenorrhea 10 . In a previous study of our group, 40% of male patients with â-thal were found to be hypogonadal 11 .…”
Section: Discussionmentioning
confidence: 56%
“…However, only 74% of patients developed primary or secondary amenorrhea 10 . In a previous study of our group, 40% of male patients with â-thal were found to be hypogonadal 11 .…”
Section: Discussionmentioning
confidence: 56%
“…Bronspiegel-Weintrob et al [13] reported that patients with abnormal puberty had higher serum ferritin levels before chelation and had received suboptimal chelation therapy (serum ferritin levels 4,734 ± 3,081 and 3,572 ± 1,870 ng/mL, respectively). Important factors for developing hypogonadism and/ or delayed puberty are a high serum ferritin level [10][11][12]. However, this study did not show such a relationship because there was no delay in puberty.…”
Section: Discussionmentioning
confidence: 60%
“…Prevalence is 40%−80% [5][6][7][8][9]. Iron overload [10][11][12] is considered one of the main factors for developing endocrine complications.…”
Section: Brief Communication (Original)mentioning
confidence: 99%
“…This endocrine disturbance is becoming less frequent nowadays with early and intensive chelation therapy. [17] The prevalence of various endocrine complications shows a difference between centers, particularly for GH deficiency, hypoparathyroidism, and hypothyroidism. [18] In the present study, the prevalence of GH deficiency in thalassemia patients was 35.9% as compared with a prevalence of 7.9% in males in a previous study[18] and up to 25% in another study.…”
Section: Discussionmentioning
confidence: 99%